90Y-FAPI-46 theranostics leads to near-complete metabolic response in 3 patients with solitary fibrous tumors - Lanzafame, Helena; Heilig, Christoph E.; Wardelmann, Eva; Desaulniers, Mélanie; Pabst, Kim Magaly; Mavroeidi, Ilektra Antonia; Pretzell, Ina; Costa, Pedro Fragoso; Nader, Micheal; Leyser, Stephan; Schuler, Martin; Bauer, Sebastian; et al. (Journal of nuclear medicine, 2025)
Visual Abstract - Solitary fibrous tumor (SFT) is a rare soft-tissue sarcoma with limited treatment options, especially in advanced or metastatic cases. Fibroblast activation protein α (FAPα) is overexpressed in certain sarcomas, including SFTs, making it a promising target for diagnostics and radiopharmaceutical therapy (RPT). We present the cases of 3 patients with metastatic SFTs who, after exhausting standard treatments, underwent molecular profiling and showed elevated FAPα expression. Methods: Messenger RNA and protein expression of FAPα were examined in biopsy samples from 3 patients participating in the Molecularly Aided Stratification for Tumor Eradication Research program, a multicenter observational study focused on biology-driven stratification of adults with advanced cancer. Messenger RNA expression levels were quantified as transcripts per million, with RNA extraction, sequencing, and data processing performed using established protocols. Protein expression was assessed and stained with FAPα immunohistochemistry using a recombinant anti-FAPα antibody. Following the recommendation of the molecular tumor board, these patients received 90Y-labeled fibroblast activation protein inhibitor (FAPI)-46 RPT because of the high uptake observed in 68Ga-FAPI-46 PET/CT scans. Results: 90Y-FAPI-46 RPT led to substantial clinical benefits, including metabolic resolution and symptom relief, with disease control confirmed using RECIST and PERCIST. Treatment was well-tolerated, with only minor adverse events observed. Conclusion: Our findings underscore the utility of FAPα screening as a predictive biomarker and the potential of FAP-targeted RPT as a viable treatment for advanced SFT.
Online veröffentlicht: Jul. 24, 2025
Im Text ist "90" hochgestellt
Gesehen am 29.01.2026